2019
DOI: 10.1007/s00586-019-05925-2
|View full text |Cite
|
Sign up to set email alerts
|

ISSLS PRIZE IN BIOENGINEERING SCIENCE 2019: biomechanical changes in dynamic sagittal balance and lower limb compensatory strategies following realignment surgery in adult spinal deformity patients

Abstract: Study design A longitudinal cohort study. Objective To define a set of objective biomechanical metrics that are representative of adult spinal deformity (ASD) post-surgical outcomes and that may forecast post-surgical mechanical complications. Summary of background data Current outcomes for ASD surgical planning and post-surgical assessment are limited to static radiographic alignment and patient-reported questionnaires. Little is known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…On further examination of the corresponding kinematic curve ( Figure 4 ), peak hip flexion seems to be the most affected in ASD-sag. This corroborates results by Bailey et al who had previously demonstrated that ASD patients had a decreased peak of hip flexion during sit-to-stand, along with an increased energy expenditure at this level ( Bailey et al, 2019 ). Limitation in hip flexion could serve to prevent additional forward bending of the trunk in the sitting position and during the transition from sitting to standing, since ASD-sag already present with an increased trunk flexion during motion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On further examination of the corresponding kinematic curve ( Figure 4 ), peak hip flexion seems to be the most affected in ASD-sag. This corroborates results by Bailey et al who had previously demonstrated that ASD patients had a decreased peak of hip flexion during sit-to-stand, along with an increased energy expenditure at this level ( Bailey et al, 2019 ). Limitation in hip flexion could serve to prevent additional forward bending of the trunk in the sitting position and during the transition from sitting to standing, since ASD-sag already present with an increased trunk flexion during motion.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, Bailey et al used a 3D depth-camera to describe motion kinematics and kinetics from 15 ASD patients, both pre- and postoperatively, compared with 10 controls. They showed that ASD patients had increased peak sagittal vertical axis (SVA) during sit-to-stand as well as increased lumbar and lower limb torques, which could be corrected by surgical interventions ( Bailey et al, 2019 ). However, the segmental motion of the spine was not analyzed and further subdivision of the ASD population according to the type of spinal deformity was not possible due to the small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Second, due to the lack of apparatus, we did not take whole spine X-rays including the lower extremity. Hence, we could not evaluate knee and hip joint flexion, which might have been used to compensate for sagittal imbalance [34]. Despite these limitations, this is the first report describing the correlation between anterior spinal surgery and changes in sagittal alignment, which might contribute to preoperative planning in OVF patients.…”
Section: Discussionmentioning
confidence: 98%
“…Analyzing intersegmental moments in these patients could be of great interest. Recently, Bailey et al [25] reported the results of a biomechanical study that evaluated peak sagittal vertical axis, forces, and muscular moments at various joints. According to their results, a significant improvement of dynamic sagittal balance metrics was observed after surgical correction in the setting of adult spinal deformity.…”
Section: Discussionmentioning
confidence: 99%